Supernatural Beings and Their Appropriation of Knowledge and Power in The Seafarer by Conor McPherson and Woman and Scarecrow by Marina Carr - Koneczniak, Grzegorz (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2020)
This article is a comparative analysis of Woman and Scarecrow by Marina Carr and The Seafarer by Conor McPherson from a hauntological perspective. It aims at discussing the influence of supernatural beings on mortal protagonists as well as addressing the configurations of power and knowledge formed between the characters. Woman and Scarecrow follows the final moments of a dying woman accompanied by the mysterious figure of Scarecrow, who is hidden from other characters. The verbal exchanges between Scarecrow and Woman will be interpreted as a manifestation of the apparent power possessed by the former, the ambiguous supernatural figure, over the latter, a human being, in terms of appropriating the knowledge about the woman’s past. In McPherson’s The Seafarer, a mysterious relationship develops between Sharky and Mr. Lockhart, who knows about Sharky’s past, too. This paper will demonstrate both similarities and differences in the way in which Carr and McPherson make use of supernatural beings that manipulate human characters in the most crucial moments of their lives and will situate the two plays within the recent rise of interest in spectrality in Irish drama.